Geochemical features of groundwater in the South Urals - R. F. Abdrahmanov; V. G. Popov (Известия высших учебных заведений: Геология и разведка)
This paper gives an analysis and generalization of the data on groundwater chemical and gas composition, located deep in the largest tectonic structures of the Urals. The distribution of groundwaters by the degree of mineralization and composition is subjected to the normal vertical hydrogeochemical zonation. Calcium chloride brines are found in the Paleozoic and Late Proterozoic sedimentary, metamorphic and volcano-sedimentary complexes at a depth of 3-5 km. Their origin is associated with sedimentation processes occurred in talassogenic basins with different salinity gradients and with subsequent metamorphism of the surrounding rocks due to the epigenetic processes.